The problem of authorship (author and the literary work of art) - Tasevska Hadji Boshkova, Iskra (Institute of Knowledge Management, 2019)
This paper represents an attempt to systematize the various presumptions concerning the author of a certain literary work of art. At the same time, it re-evaluates the standard and schematized terms regarding literature as a whole, the essence of literary language, the existence of literary genre, etc. A theoretical possibility of this kind of re-evaluation is the re-examination of the phenomenon called literature, as well as the investigation of its boundaries, that cannot be confined to the Western centric hypothesis of literary language, or the existence of literary genres. Our postmodern epoch has confirmed the necessity of certain extension of the approach to what is called literature, as well as its field of study. Today, it is almost impossible to frame the discrete elements, or the factors that acknowledge the thesis of the independent position of literature in the social process. On the other hand, this kind of relativization of terms has led to the need for more differentiated and more detailed assumption of a certain minimum of elements or aspects, that differentiate literature and artistic creations overall from the other non-artistic phenomena (or the ones that cannot claim this kind of attribute). This kind of necessity takes us back to the re-evaluation of the established notions and categories, since without their existence it is not possible to scientifically analyze literature and literary process overall (even if that analysis is being developed through cultural terms). Hence, the re-investigation of modern and postmodern critical analyses is one of the possible methods to evaluate and examine the key concepts regarding the author and its work. At the same time, the analysis of the problem of authorship does not only concern literary theory, although it poses this question as the most dominant one, since its main preoccupation is the search for meaning of literary work, as well as the way this meaning is being diffracted in various instances of the text. On the other hand, an essential part of this process is the necessity to reveal the person that created this meaning. It is undoubtedly true that this so-called person can in fact represent a shadow of the various unconfirmed, but present voices of a certain epoch or cultural region, from which this man or woman, signed as an author of the text or work, comes from. The proper investigation of the discursive identity called literary work thus requires an exploration of numerous discrete nuances, through which different social and historical accents come into being. However, this does not mean that the critic is a person that is in constant search of lost meanings. In fact, literary theory, spreading the field of its analyses, has provoked the unstoppable interest of its researchers and their necessary investigation of other social sciences and humanities, as well as their different approaches to the broad field, where cultural phenomena come into being.
Keywords: author, literature, literary work of art, discourse, subjectivity.